2021
DOI: 10.3390/ijerph182412972
|View full text |Cite
|
Sign up to set email alerts
|

Bioelectrical Impedance Vector Analysis of Young Elite Team Handball Players

Abstract: Team handball is a highly dynamic sport where physical demands differ between categories and roles. Thus, physical characteristics are fundamental for the final performance. This study aims to (a) characterize a sample of young male and female elite team handball players with a non-athletic reference population; (b) to generate their 50%, 75%, and 95% percentiles of the bioelectrical variables. The study included 55 young elite team handball players (Males, n = 37, age = 17.0 ± 1.2 yrs, height = 185.8 ± 7.3 cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Thus, handball practitioners have a probability of 1.78 of presenting a PhA higher than the median of the present study. PhA values of 7.5º±0.5 were found for the sample in a study with 19 male handball athletes (age = 16.5±0.6) for the U17 level [36], where the authors suggested sex, chronological age, and selection of an intense routine based on physical training may determine the specificity of BIA properties in handball players. When considering the rugby modality, it was observed that most players have a probability of 2.01 to generate a PhA greater than 7.7º, mainly for the age group above 16 years, which can be explained by the average results of the strength tests (i.e., SJ, CMJ, and HGS), which are superior to those of the other modalities.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, handball practitioners have a probability of 1.78 of presenting a PhA higher than the median of the present study. PhA values of 7.5º±0.5 were found for the sample in a study with 19 male handball athletes (age = 16.5±0.6) for the U17 level [36], where the authors suggested sex, chronological age, and selection of an intense routine based on physical training may determine the specificity of BIA properties in handball players. When considering the rugby modality, it was observed that most players have a probability of 2.01 to generate a PhA greater than 7.7º, mainly for the age group above 16 years, which can be explained by the average results of the strength tests (i.e., SJ, CMJ, and HGS), which are superior to those of the other modalities.…”
Section: Discussionmentioning
confidence: 94%
“…2,3 In addition, multiple variables need to be taken into account to design specific training programmes and evaluate athletes' state, such as maximal capacities, 4 autonomic nervous system (ANS) response, and psychophysiological states. [5][6][7][8][9] For instance, motorsports require high capacity to respond and adapt to the continuous changes in the environmental situation during a race. 10 The different stressors representing motorsports, (e.g.…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 3 In addition, multiple variables need to be taken into account to design specific training programmes and evaluate athletes’ state, such as maximal capacities, 4 autonomic nervous system (ANS) response, and psychophysiological states. 5 9 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, showed an inverse correlation with the ratio of extracellular to intracellular water (ECW/ICW), independently of the BIVA approach [ 14 ]. BIVA has been studied in many sports [ 15 ], plotting the athletes within a tolerance ellipse of a given reference population, performing intra- or inter-group comparisons, monitoring athletes through a competitive season [ 16 , 17 ], or creating new tolerance ellipses for specific sports population, as it has been made in soccer players and referees [ 18 , 19 ], cyclists [ 20 ], synchronized swimmers [ 21 ], handball players [ 22 ] or natural bodybuilders [ 23 ]. To our knowledge, this is the first study analyzing the complete bioelectrical profile in CrossFit®.…”
Section: Introductionmentioning
confidence: 99%